Application of Positive Affirmation Therapy to Improve The Quality of Life in Patients with Low Self-Esteem at dr. RM Soedjarwadi Mental Hospital Klaten - Anggraini, Intan; Gati, Norman Wijaya; Reknoningsih, Wahyu (Jurnal Kesehatan Komunitas Indonesia, 2025)
Background: Low self-esteem is a psychological problem commonly experienced by patients with mental disorders, particularly schizophrenia, which can negatively impact their quality of life. Positive affirmation therapy is one effective non-pharmacological intervention to enhance both quality of life and self-esteem. This therapy works by embedding positive thoughts through repeated self-statements to shape a better self-perception, boost self-confidence, and reduce negative thinking patterns. Objective: This study aims to determine the effectiveness of positive affirmation therapy in improving the quality of life of patients with low self-esteem at the Flamboyan Ward of dr. RM Soedjarwadi Mental Hospital Klaten. Method: This research employed a descriptive case study approach involving two patients diagnosed with low self-esteem. The positive affirmation therapy was administered twice daily for three consecutive days. The patients’ quality of life was assessed before and after the intervention using the WHOQOL-BREF instrument. Results: The results showed increased quality of life in both patients. Patient B improved from a WHOQOL score of 50 (moderate) to 75 (good), while patient A improved from 50 (moderate) to 100 (excellent) after receiving the positive affirmation therapy. Conclusion: Positive affirmation therapy has proven to be an effective, safe, and simple non-pharmacological method for improving the quality of life in patients with low self-esteem. This intervention can be a supportive therapy in mental health nursing, especially in strengthening patients' self-concept.